STRATEGY FOR PREVENTING DRUG ABUSE AMONG ADOLESCENTS BY THE NATIONAL UNITY AND POLITICS AGENCY OF SOUTH LABUHANBATU REGENCY - Nani Chairani Lestari Lubis; Tengku Irmayani; Agus Suriadi (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2026)
This research aims to describe and analyze strategies for preventing narcotics abuse by the South Labuhanbatu Regency National and Political Unity Agency (Bakesbangpol) and identify obstacles in its implementation. The main problem addressed by this research is that South Labuhanbatu Regency ranks among the top five areas in North Sumatra Province for narcotics danger, with 371 suspects reported between 2023 and October 2024, primarily from the productive age group and teenagers. The research method used is a descriptive qualitative approach. Data collection techniques were carried out through triangulation, which included semi-structured interviews with key informants, observation, and documentation studies. "Data analysis" refers to Hunger and Wheelen's strategic management model, which includes four elements: environmental observation, strategy formulation, strategy implementation, and evaluation and control. The research results show that at the environmental observation stage, Bakesbangpol has strong operational facilities but is weak in the quantity and competency of human resources and does not yet have a narcotics specialization unit. The strategy formulation is considered to be still general and not sharp enough, as the target performance indicators (150 students) are very disproportionate compared to the youth population, which reaches 63,272 people. The implementation stage was hampered by budget limitations, with realization of only 61% and a long gap in outreach activities since 2022. At the evaluation stage, data asymmetry was found because performance achievements were not included in the 2024 Performance Accountability Report. In conclusion, the prevention strategy has not been effective and consistent due to weak policy focus and budget support. Researchers suggest the establishment of the South Labuhanbatu BNNK and a special youth unit at Bakesbangpol to increase the effectiveness of prevention on an ongoing basis. Keywords: Prevention, Narcotics, Youthl, Strategic Management.